INOVASI LAYANAN PERPUSTAKAAN UMUM KABUPATEN TANAH DATAR SELAMA MASA PANDEMI COVID-19 - Muhammad Fadhli (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
As a result of the corona virus pandemic or Covid-19 spreading and hitting Indonesia since 2020, forcing the Government of the Republic of Indonesia to issue Government Regulation of the Republic of Indonesia No. 21 of 2020 concerning Large-Scale Social Restrictions on all activities involving large numbers of citizens. According to Law no. 25 of 2009 concerning Public Services states that every institution / agency engaged in public services including public libraries must have minimum service standards and pay attention to the rights and obligations of each party, both the agency itself and the community as parties who take advantage of these public services. activities and the people served can still take advantage of these services in the midst of a pandemic situation. This research uses a qualitative approach with a case study method. As for the data collection method using interviews with librarians at the Public Library of Tanah Datar Regency. In addition to interviews, data collection also uses observation and documentation methods to obtain valid data. This research was conducted in November-December 2021. Public Library of Tanah Datar Regency is located on Jl. Sultan Alam Bagagarsyah, Batusangkar. Public Library of Tanah Datar Regency is still operating as usual but by implementing strict health protocols such as maintaining distance, wearing masks and washing hands. The results showed that the information needs of the people of Tanah Datar Regency were quite high, indicated by the large number of people who still visited the library. Libraries need to immediately develop automated libraries and digital libraries and increase digital collections so that they can reach a wider audience as well as to anticipate a pandemic situation that lasts for a long time.